The Significance of Preservation of Memories in Yasunari Kawabata’s God’s Bones - Wijaya, Kusuma; Pangestu, Imelza Novia Rakhmadani; Wulandari, Siti; Hariyono, Hariyono; Pasopati, Rommel Utungga (KIRYOKU, 2024)
This paper investigates the matters of preservations of memories in Yasunari Kawabata’s God Bones. This flash fiction tells about a girl who has never married but already has a baby in her womb. That condition reminds her and her surroundings about the history of the past, especially when she gives the ashes of the baby's bones  to many men. Through qualitative method, this study explains about a person's memory that has happened and will continue to overshadow her. In analysis, memories are not merely collections of events or repositories of knowledge, those are also identities that shape further decision making processes. In conclusion, this story shows how memories link past with present and future. Those are the results of circulation of signs, regarding various concepts and contexts of the past.